British union-catalogue of periodicals : incorporating world list of scientific periodicals - Gascoigne J.; Porter, Kenneth I.; British Library; National Central Library (Great Britain) (London : Butterworths, 1977)
"The British union-catalogue of periodicals (BUCOP) in its new form is concerned with the recording of new periodical titles for the period in and after 1960."
Edited 1964-69 by K.I. Porter
Includes bibliographical references and index
Edited 1964-73 for the National Central Library; 1974-80 for the British Library
"Incorporating World list of scientific periodicals," which still appears as Cumulative annual volume of scientific titles
1
Keywords: Periodicals -- Bibliography -- Union lists